Development of Interactive Learning Media Based on Geogebra Classic 6 to Improve Mathematical Communication on Solid Geometry - Hendri Johan Tambunan; Edi Syahputra (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine: Showing an interactive learning media of mathematics on students' mathematical communication skills as a whole, The magnitude of the influence of using Geogebra-based interactive learning media on mathematical communication abilities based on educational level, the magnitude of the effect of using interactive mathematical learning media on mathematical communication skills based on previously used interactive learning media, the large influence of the use of interactive learning media plays an important role in systematic mathematical methods, the large effect of the use of interactive learning media on mathematical communication skills is imaginative to mathematical communication based on the mathematical ability that is measured. This study uses the addie model. This sampling technique is highly influential using the Addie model and obtained 20 studies that match the criteria. This data collection technique uses freetest and posttest with the help of Geogebra Classic 6 software and the help of Microsoft powerpoint. The results of this data experiment show that: overall this interactive learning media has a major influence on students' mathematical communication abilities.